Constitutive, institutive and up-regulation of carotenogenesis regulatory mechanism via in vitro culture model system and elicitors - Othman, Rashidi; Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian (2014)
Every single step in the pathway of carotenogenesis in the leaves or any part of the plants is regulated and controlled by specific genes. It was inferred that these genetic components would be inherited by either undifferentiated (callus) or differentiated (in vitro shoot) cells since they were initiated from their respective intact plants. Thus, the in vitro cultures are most likely to develop and respond similarly upon various internal and external stimuli like the intact plants. Therefore, this study was aimed at establishing in vitro cultures as potential research tool to study the regulatory mechanism of the carotenoid biosynthesis in medicinal species through a controlled environment. This establishment would be beneficial as researchers in this field could overcome problems encountered in researches using intact plants. Via HPLC analysis, it was found that different types of cultures accumulated different types of carotenoid as compared to their intact plants, accordingly. The results obtained in this study suggested that the key factors which involved in regulatory mechanisms of individual carotenoid biosynthesis in a particular biology system of plants can be assessed and predicted. On top of that, further exploration and manipulation of the environmental conditions is made possible for enhancement or enrichment of certain carotenoid of interest in food crops without altering the genes and thus issues regarding the introduction of genetically modified (GM) crops into natural environment and acceptability of consumers towards GM crops could be minimized.